KEABSAHAN PERJANJIAN PENGIKATAN JUAL BELI YANG MENGANDUNG KLAUSUL KUASA MUTLAK SEBAGAI PEMINDAHAN HAK ATAS TANAH - Angel Halim; Mia Hadiati (Jurnal Hukum Adigama, 2021)
A sale and purchase agreement (PPJB) is often carried out in the process of buying and selling land, which there is an absolute power of attorney. There are pros and cons regarding the use of absolute power of attorney that there are problems regarding the validity of the PPJB which contains an absolute power clause as a transfer of rights to land and legal consequences of prohibiting the use of absolute power as a transfer of rights to land. This research uses normative legal research methods and uses data collection or processing techniques through literature review and interviews with related sources. The results of this study are that the use of absolute power in the sale and purchase agreement is valid as long as the power granted is contained in the principal agreement. The use of absolute power that is prohibited is the granting of power that does not follow the main agreement, meaning that this power is independent. The legal consequence of the use of absolute power in the transfer of land rights is that the absolute power can be canceled and null and void by law, however such absolute power can only be canceled by a judge's decision and generally will occur if there is a dispute. The suggestion is that there needs to be clear rules governing absolute power in more detail so that the pros and cons regarding this absolute power are resolved, land deed officials should be more careful when going to use absolute power.